CFD ANALYSIS OF LAMINAR FORCED CONVECTIVE HEAT TRANSFER FOR TiO2/WATER NANOFLUID IN A SEMI CIRCULAR CROSS SECTIONED MICRO CHANNEL - Kaya, H.; Ekiciler, Recep; Arslan, Kamil (My University, 2019)
In this study, forced convection flow and heat transfer characteristics of TiO2/water nanofluid flow with different nanoparticle volume fractions (1.0%, 2.0%, 3.0% and 4.0%) in semi circular cross sectioned microchannel was numerically investigated. The three dimensional study was conducted under steady state laminar flow condition where Reynolds number changing from 100 to 1000. CFD model has been generated by using ANSYS FLUENT 15.0 software based on finite volume method. The flow was under hydrodynamically and thermally developing flow condition. Uniform surface heat flux boundary condition was applied at the bottom surface of the micro channel. The average and local Nusselt number and Darcy friction factor values were obtained using numerical results. Also, the effects of using nanofluid on local values of Nusselt number and Darcy friction factor were investigated. Numerical results indicate that the increasing of nanoparticle volume fraction of nanofluid, the average Nusselt number increases; however, there is no significant variation in average Darcy friction factor.
Keywords: Termodinamik; Fizikokimya